pH-Driven Self-Assembly of Acidic Microbial Glycolipids - Baccile, Niki (Langmuir : the ACS journal of surfaces and colloids, 2016)
Microbial glycolipids are a class of well-known compounds, but their self-assembly behavior is still not well understood. While the free carboxylic acid end group makes some of them interesting stimuli-responsive compounds, the sugar hydrophilic group and the nature of the fatty acid chain make the understanding of their self-assembly behavior in water not easy and highly unpredictable. Using cryo-transmission electron microscopy (cryo-TEM) and both pH-dependent in situ and ex situ small angle X-ray scattering (SAXS), we demonstrate that the aqueous self-assembly at room temperature (RT) of a family of β-d-glucose microbial glycolipids bearing a saturated and monounsaturated C18 fatty acid chain cannot be explained on the simple basis of the well-known packing parameter. Using the "pH-jump" process, we find that the molecules bearing a monosaturated fatty acid forms vesicles below pH 6.2, as expected, but the derivative with a saturated fatty acid forms infinite bilayer sheets below pH 7.8, instead of vesicles. We show that this behavior can be explained on the different bilayer membrane elasticity as a function of temperature. Membranes are either flexible or stiff for experiments performed at a temperature respectively above or below the typical melting point, TM, of the lipidic part of each compound. Finally, we also show that the disaccharide-containing acidic cellobioselipid forms a majority of chiral fibers, instead of the expected micelles